Smart Material Characterization by Thermal and Structural Analysing Techniques - Unlu, N.; Canbay, C. Aksu; Ozkul, I; Karaduman, O. (Amer Inst Physics, 2019)
Copper based alloys are preferred because of their excellent electrical and thermal energy transmission, corrosion resistance, lattice structure and being a much more economical alternative instead of NiTi shape memory alloys. In this study, thermal and structural properties of Cu-based shape memory alloy were investigated. The characteristic austenite and martensite transformation temperatures were determined by Differential Scanning Calorimetry (DSC). Structural properties were investigated by X-Rays analysis (XRD) and the results obtained were concluded to be in parallel with the literature.
35th International Physics Congress of the Turkish-Physical-Society (TPS) -- SEP 04-08, 2019 -- Bodrum, TURKEY
Keywords: SMA; Thermal analysis; Structural analysis